"Reason Run Riot": Holmes and the Ripper in A Study in Terror and Murder by Decree. Issue 2 (3rd April 2017) - Burnip, Richard
Abstract: Sherlock Holmes first appeared in print just months before the "Jack the Ripper" murders began. Both the fictional detective and the real-life killer were firmly established in popular imagination by the early 1890s. Arthur Conan Doyle himself took considerable interest in the case, visiting the crime scenes and looking at some of the police evidence. Elements from the crimes found their way into his Holmes stories. An imagined confrontation between Holmes and the Ripper was almost inevitable. This article looks at two films A Study in Terror (Dir. James Hill, 1965 ) and Murder by Decree (Dir. Bob Clark, 1979 ) and their markedly different approaches to the contest between sleuth and murderer. It examines the parallel celebrity of Holmes and the Ripper, considers both films in the contexts of their respective periods, contrasts the decisions taken over characters who appear in both projects, and examines how different theories of the murders influenced both scripts. This article concludes by investigating how the films' interpretations of Holmes, Watson, Mycroft, and Lestrade influenced later portrayals.